2019
DOI: 10.1021/acsami.9b19206
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Route toward Superior Photoresponse of UV-Laser-Treated TiO2 Nanotubes

Abstract: Titanium dioxide nanotubes gain considerable attention as a photoactive material due to chemical stability, photocorrosion resistance, or low-cost manufacturing method. This work presents scalable pulsed laser modification of TiO2 nanotubes resulting in enhanced photoactivity in a system equipped with a motorized table, which allows for modifications of both precisely selected and any-large sample area. Images obtained from scanning electron microscopy along with Raman and UV–vis spectra of laser-treated sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 59 publications
4
37
1
Order By: Relevance
“…Nevertheless, it was stated that with the increasing value of laser energy, the rutile peaks appear in XRD patterns. That is not observed in here, as the chosen energy fluence is high enough only to overcome the nucleation barrier for the transformation of TiO2NTs into anatase [26]. However, when the same sample is processed in vacuum (Figure 4b), no amorphous region is observed and anatase (101) peak can be seen at a penetration depth of ca.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, it was stated that with the increasing value of laser energy, the rutile peaks appear in XRD patterns. That is not observed in here, as the chosen energy fluence is high enough only to overcome the nucleation barrier for the transformation of TiO2NTs into anatase [26]. However, when the same sample is processed in vacuum (Figure 4b), no amorphous region is observed and anatase (101) peak can be seen at a penetration depth of ca.…”
Section: Resultsmentioning
confidence: 65%
“…The impact of the nanotubes length or atmosphere conditions onto the morphology, structural and optical properties was not considered. Regarding another work that we referred to here [26], we focused only on the laser treatment of the already calcined titania and investigated the effects onto the photoelectrochemical activity. On the contrary, herein we focus onto the different titania substrates used for further laser modification: amorphous and calcined ones while the laser treatment has been carried out both in air and under vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of laser annealing on the pristine TiO 2 -NTs was studied by several authors [16,17,37,39,47]. In all cases, it was concluded that the laser fluence required to create the continuous re-solidified layer has to be higher than 40 mJ/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Among others, the ns laser pulse induces fast heating and cooling process, even above the melting point, therefore, its interaction with multi-layer composite may result in diffusion of atoms across the interphase, as well as the formation of metastable phases and structural defects [38]. That technique is extremely fast, is easy-scalable for large areas, and due to a wide range of processing parameters can be applied to various materials [39]. The modification of anatase TiO 2 -NTs electrode using Nd:YAG laser was shown to enhance charge carrier donor density over one order of magnitude and a shift of the flat-band potential up to +0.7 V vs. Ag|AgCl|0.1 M KCl [16,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation